Vaccines for a healthy future: 21st DCVMN Annual General Meeting 2020 report. Issue 18 (28th April 2021) - Pagliusi, Sonia; Hayman, Benoit; Jarrett, Stephen
Abstract: The Developing Countries Vaccine Manufacturers' Network held its 21st Annual General Meeting virtually in November 2020 given the COVID-19 pandemic. Vaccine manufacturing experts, leaders from local and global public health organizations and multilateral organizations, through diverse presentations, questions and answers, focused on the pandemic and the response of vaccine manufacturers where many are engaged in research and development and production agreements. The pandemic is expanding rapidly which makes the global availability and equitable access to safe and effective COVID-19 vaccines critical. Strategies put in place include the establishment of the Access to COVID-19 Tools Accelerator (ACT-A) within which the COVAX facility aims to distribute 2 billion COVID-19 vaccine doses by the end of 2021, with procurement mechanisms already being established. At the same time, regulatory authorities have emergency use authorizations aimed at the rapid approval of safe and effective vaccines, with a push for harmonization in regulatory approaches being advocated. The Meeting was also apprised of other innovations being developed for vaccines including multi-array patches for easier vaccine application, increased heat stability for mitigating cold chain and storage challenges, the barcoding of primary packaging for enhancing vaccine traceability, and gathering data for decision-making. Over time, these innovations will facilitate the widespread availability and equitable access of vaccines including those addressing epidemics and pandemics. In addition, a number of manufacturers described technologies they have for accelerating vaccine manufacturing and supply globally. Overall, there was agreement that manufacturers from developing countries play a critical role in the global research, development and supply of vaccines for a healthy future, with increasing collaboration and partnering between them a growing strength.